Exploring the Effects of the Long Noncoding RNA MIR205HG on PI3K Inhibitor Resistance in Breast Cancer - Vasilevski, Natali (Curtin University, 2025)
Breast cancer is a leading cause of cancer death worldwide, with nearly 21,000 cases predicted in Australia for 2024. A key driver is the PI3K pathway, often hyperactivated due to PIK3CA mutations or loss of the tumor suppressor PTEN. Resistance to PI3K inhibitors is common, but long noncoding RNAs (lncRNAs) like MIR205HG may play a role. This study found that losing MIR205HG increased resistance but made cells vulnerable to prolonged PI3K inhibition, revealing a potential therapeutic strategy.